Eradication of posterior capsule opacification: documentation of a marked decrease in Nd:YAG laser posterior capsulotomy rates noted in an analysis of 5416 pseudophakic human eyes obtained postmortem - Apple, David J.; Peng, Qun; Visessook, Nithi; Werner, Liliana; Pandey, Suresh K.; Escobar-Gomez, Marcela; Ram, Jagat; Auffarth, Gerd U. (Ophthalmology, 2020)
Objective - (1) To report the neodymium:yttrium-aluminum-garnet (Nd:YAG) laser posterior capsulotomy rate (%) of eight rigid and foldable intraocular lens (IOL) designs in a series of 5416 pseudophakic human eyes obtained postmortem, accessioned in our center between January 1988 and January 2000. (2) To identify factors that are instrumental in reducing the incidence of posterior capsule opacification, (PCO, secondary cataract) and hence the need for Nd:YAG laser posterior capsulotomy. - Design - Comparative autopsy tissue analysis. - Participants - A total of 5416 globes with posterior chamber intraocular lens (PC-IOLs) obtained postmortem received from Lions Eye Banks between 1988 and 2000. - Methods - Miyake-Apple posterior photographic technique. Special reference was given to the presence or absence of Nd:YAG laser posterior capsulotomy orifice on the posterior capsule of each eye. - Main Outcome Measures - The Nd:YAG laser posterior capsulotomy rate (%) as of January 2000 was documented. In addition, the Nd:YAG laser posterior capsulotomy rate for each lens was plotted on a monthly basis for the same period, creating a computerized trend or "timeline" for each IOL style. - Results - Relatively high Nd:YAG laser posterior capsulotomy rates ranging from 20.3% to 33.4% were noted with four relatively older designs (high incidence of implantation between 1988 and the early 1990s). Four modern foldable lOLs manufactured from silicone and acrylic materials had significantly lower Nd:YAG laser posterior capsulotomy rates ranging from 0.9% (Alcon Acrysof) to 17.1%. The difference in Nd:YAG rates among the eight IOL designs was found to be significant (P < 0.0001, chi-square test). Comparing foldable versus rigid designs, the foldable IOLs were associated with a much lower Nd:YAG laser posterior capsulotomy rate (14.1% vs. 31.1%). - Conclusions - By use of the six factors regarding surgical technique and IOL choice described in this article, we strongly believe that the overall incidence of PCO and hence the incidence of Nd:YAG laser posterior capsulotomy is now rapidly decreasing from rates as high as 50% in the 1980s to early 1990s. Surgical tools and IOLs are now available to bring these rates down to single digits. Careful application and use of these tools by surgeons can genuinely lead in the direction of virtual eradication of secondary cataract, the second most common cause of visual loss worldwide.